Acrolein Exposure Is Associated With Increased Cardiovascular Disease Risk. Issue 4 (6th August 2014) - DeJarnett, Natasha; Conklin, Daniel J.; Riggs, Daniel W.; Myers, John A.; O'Toole, Timothy E.; Hamzeh, Ihab; Wagner, Stephen; Chugh, Atul; Ramos, Kenneth S.; Srivastava, Sanjay; Higdon, Deirdre; Tollerud, David J.; et al.
Abstract : Background: Acrolein is a reactive aldehyde present in high amounts in coal, wood, paper, and tobacco smoke. It is also generated endogenously by lipid peroxidation and the oxidation of amino acids by myeloperoxidase. In animals, acrolein exposure is associated with the suppression of circulating progenitor cells and increases in thrombosis and atherogenesis. The purpose of this study was to determine whether acrolein exposure in humans is also associated with increased cardiovascular disease (CVD) risk. Methods and Results: Acrolein exposure was assessed in 211 participants of the Louisville Healthy Heart Study with moderate to high (CVD) risk by measuring the urinary levels of the major acrolein metabolite—3‐hydroxypropylmercapturic acid (3‐HPMA). Generalized linear models were used to assess the association between acrolein exposure and parameters of CVD risk, and adjusted for potential demographic confounders. Urinary 3‐HPMA levels were higher in smokers than nonsmokers and were positively correlated with urinary cotinine levels. Urinary 3‐HPMA levels were inversely related to levels of both early (AC133 + ) and late (AC133 − ) circulating angiogenic cells. In smokers as well as nonsmokers, 3‐HPMA levels were positively associated with both increased levels of platelet–leukocyte aggregates and the Framingham Risk Score. No association was observed between 3‐HPMA and plasma fibrinogen. Levels of C‐reactive protein were associated with 3‐HPMA levels in nonsmokers only. Conclusions: Regardless of its source, acrolein exposure is associated with platelet activation and suppression of circulating angiogenic cell levels, as well as increased CVD risk.